Neutrophil Extracellular Traps and Microcrystals - Balázs Rada (Journal of Immunology Research)
Neutrophil extracellular traps represent a fascinating mechanism by which PMNs entrap extracellular microbes. The primary purpose of this innate immune mechanism is thought to localize the infection at an early stage. Interestingly, the ability of different microcrystals to induce NET formation has been recently described. Microcrystals are insoluble crystals with a size of 1–100 micrometers that have different composition and shape. Microcrystals have it in common that they irritate phagocytes including PMNs and typically trigger an inflammatory response. This review is the first to summarize observations with regard to PMN activation and NET release induced by microcrystals. Gout-causing monosodium urate crystals, pseudogout-causing calcium pyrophosphate dehydrate crystals, cholesterol crystals associated with atherosclerosis, silicosis-causing silica crystals, and adjuvant alum crystals are discussed.